The relationship between the vaginal and vulvar microbiomes and lichen sclerosus symptoms in post-menopausal women - Oluwatobiloba A. Taylor; Kenzie D. Birse; D.’Atra J. Hill; Samantha Knodel; Laura Noel-Romas; Anna Myers; Jean Marino; Adam D. Burgener; Rachel Pope; Christina Farr Zuend (Scientific Reports)
Abstract Lichen sclerosus is a chronic inflammatory condition of unknown etiology that affects the genital and extragenital skin, which can lead to sexual dysfunction and has been associated with vulvar cancer. The vaginal microbiome has a critical role in gynecologic health, but little is known about the microbiome in lichen sclerosus. This study investigated the vaginal and vulvar microbiomes of 27 post-menopausal women with lichen sclerosus. The most abundant genera detected in the vaginal microbiome were Lactobacillus, Gardnerella, and Anaerococcus, while Lactobacillus, Anaerococcus, and Staphylococcus were the most abundant in the vulvar microbiome. The vaginal samples clustered into two main groups, Lactobacillus dominant (n = 6, > 50% microbiome Lactobacillus) and polymicrobial (n = 21) with no dominant genus. The vulvar samples were mainly polymicrobial (n = 25). Actinomyces, Anaerococcus, and Ezakiella in the vaginal microbiome and Actinomyces and Ezakiella in the vulvar microbiome were significantly associated with lichen sclerosus symptoms (adjusted p < 0.05). In this population of post-menopausal women with lichen sclerosus the majority have diverse, non-Lactobacillus dominant microbiomes, which is considered less optimal for gynecologic health based on studies of pre-menopausal women. Actinomyces, Ezakiella, and Anaerococcus were associated with lichen sclerosus symptoms. Understanding the role of these bacteria in lichen sclerosus pathogenesis will be an essential future investigation.